Government Policy as a Variable to Control the Influence of Exchange Rates, Interest Rates, and Inflation on ICI - Lisma Herawati; Rudolf Lumbantobing; Lambok D.R. Tampubolon (GoAcademica Research & Publishing, 2023)
This research explores how inflation, exchange rates and interest rates impacted the Jakarta Composite Index between 2016 and 2022. It also aims to determine the changes in the impact of exchange rates, inflation and interest rates on the Index before and after the implementation of government policies. Key policies examined include the enforcement of large-scale social restrictions (PSBB) in April 2020 due to the pandemic of covid 19, and a reduction of the BI7DRR interest rate by 25 basis points in October 2019. The study employs a quantitative experimental hypothesis and gathers data from www.bps.go.id, www.bi.go.id, and www.kemendag.go.id. Using purposive sampling for analysis, and SPSS version 26 for data processing, the study reveals that in the absence of government intervention, exchange rates, interest rates, and inflation significantly influence the Jakarta Composite Index. Specifically, while this exchange rate positively affects the Index, interest rates have a negative impact, and inflation also contributes positively. Conversely, following the PSBB policy in April 2019, both the exchange rate and interest rates negatively affected the Index, with exchange rate showing a significant negative impact, interest rate continuing to affect negatively, and inflation still having a positive influence.